Representaciones de la herejía y discurso político en las entradas de la Corte lisboeta: de la Unión ibérica a la alianza con la Inglaterra anglicana - Borja Franco Llopis; Iván Rega Castro (Potestas. Estudios del Mundo Clásico e Historia del Arte, 2020)
The aim of this paper is to reconstruct the iconography of the heresy and Protestantism in the ephemeral decorations of the Royal entries in Portugal during the Early Modern period. It will be also analysed how these iconographical images changed thanks to the new political alliance between the Kingdom or Portugal and the Anglican England.